The presentation pattern and surgical strategies in bronchopulmonary carcinoid tumors: a multicenter experience in a low-income country - Deme, Workneh Tesfaye; Merine, Seyoum Kassa; Wadaja, Desalegn Fekadu; Gemeda, Abdela Hayato; Demissie, Meklit Tamrat; Bahta, Mahlet Tesfaye; Reta Demissie, Wondu (Frontiers in Surgery, 2024)
Background Bronchopulmonary carcinoid tumors include typical and atypical carcinoids, with typical carcinoids accounting for 80%–90% of these types of tumor. The primary curative treatment for these tumors is surgical resection. To our knowledge, there are limited studies on the presentation patterns and treatment strategies of bronchopulmonary carcinoid tumors in Africa. Objective To determine the presentation patterns and surgical strategies in bronchopulmonary carcinoid tumors in patients treated at multicenters in Ethiopia from January 2018 to December 2023. Materials and methods A 5-year retrospective cross-sectional study was conducted using medical records and pathology record reviews of patients operated on in Tikur Anbessa Specialized Hospital, Menelik II Hospital, and Saint Peter's Specialized Hospital from 1 January 2018 to 31 December 2023. The completeness of the data was checked before being entered into EpiData version 4.6.1, and analysis was conducted using SPSS version 29. Logistic regression was applied to depict the association of the histological pattern with its predictors. A P-value of <0.05 was considered significant for the association of variables. Results A total of 62 patients with bronchopulmonary carcinoid tumors were included in the study with a mean age of 35.29 ± 12.26 years ranging from 14 to 67 years, in which more than half [37 (56.5%)] were females, with a male-to-female ratio of 1:1.3. The majority of the patients were non-smokers (90.3%) and symptomatic (98.4%), with a mean duration of symptoms of 29.7 ± 26 months, ranging from 3 to 156 months. Nearly half of the patients (48.4%) were treated for pulmonary tuberculosis before a diagnosis of carcinoid tumor was made. The majority of the patients underwent surgery by open posterolateral thoracotomy (98.4%), and pneumonectomy was the most common (38.7%) resection performed. Typical carcinoids were observed in 85.5% of patients. Age, smoking history, duration of symptoms, location of tumors, and lymph node status were statistically associated with histological patterns. Recommendation Based on our study findings, improving physician awareness on the clinical presentation of carcinoid tumors, training for surgeons in less invasive surgical approaches, and further nationwide studies are recommended.